A study of wire breakup and in-flight particle behaviour during wire flame spraying of aluminium - Lunn, G.D.; Riley, M.A.; McCartney, D.G. (Springer, 2017)
Although wire flame spraying has been used for many years, there has been relatively little attention given to understanding the process dynamics. In this work, imaging of the molten wire tip, particle imaging using the Oseir Spray Watch system and particle capture (wipe tests) have all been employed to quantify plume behaviour. Aluminium wire feedstock is melted and then breaks-up close to the exit of the spray nozzle in a non-axisymmetric manor. The mean velocity and diameter of the particles detected by the Spray Watch system change little with stand-off distance with values of approximately 280 m/s and 70 μm respectively for the spray parameters employed. The particle diagnostic system could not detect particles ⪅ 45 μm in diameter and it is estimated that these account for no more than 53 % of the sprayed material. Overall, wire flame spraying generates a surprisingly stable particle stream.